PREVALENCE OF OVERWEIGHT AND ASSOCIATED DEMOGRAPHIC AND ECONOMIC FACTORS AMONG ADOLESCENTS OF MANAUS, THE LARGEST CITY OF NORTHERN BRAZIL - Pinto, André de Araújo; Barbosa, Rita Maria dos Santos Puga; Nahas, Markus Vinicius; Pelegrini, Andreia (Journal of Health Care, 2018)
Introduction: Estimates of overweight prevalence among Brazilian adolescents have been made in several states, but the scarcity of data about the adolescents from Northern region is evident. ObjecÂtive: To estimate the prevalence of excess weight and its association with demographic and economic factors in adolescents from Manaus, Amazonas, Brazil. Methodology: A cross-sectional study was conducted among 1,107 adolescents (627 girls), with ages ranging from 14 to 19 years, in Manaus city, in the year 2011. Overweight was classified by using body mass index and adopting the cut-off points for gender and age recommended by the International Obesity Task Force (IOTF). The independent variables were gender, age, household income and educational level of the mother. Associations were tested using Poisson regression. Results: The prevalence of overweight was 37.4% (95% CI = 34.6-39.8). The adolescents who are male (PR = 2.54; 95% CI = 2.12-3.03), the ones who are 14 to 16 years old (PR = 1.23; 95% CI = 1.06-1.44), and the children of mothers with higher level of education (PR = 1.66; 95% CI= 1.44-1.92) were more likely to have excess weight when compared to the female ones, to those aged 18 to 19 years and to children of mothers with lower schooling level, respectively. Conclusion: The overweight prevalence was high in relation to other Brazilian studies. The preventive measures for excess weight should be directed mainly to male adolescents, to the youngers and to children of mothers with higher education level.